PENINGKATAN DISOLUSI FUROSEMIDA DENGAN PEMBENTUKAN KOMPLEKS INKLUSI MELALUI KOPRESIPITASI MENGGUNAKAN β- SIKLODEKSTRIN - Nurul Ainah; Yandi Syukri; M. Hatta Wibowo (Universitas Islam Indonesia, 2005)
ABSTRACTFurosemide is a diuretic drug, which is insoluble in water. Due to this condition, it is needed away to increase the dissolution rate with forming of inclusion complex in copresipitation systemwhich produce as solid dispersion product using β-cyclodextrin carrier. The copresipitation systemwas made up of 1 : 0,5; 1 : 1; 1 : 1,5 and 1 : 2 variation concentration of furosemide- β-cyclodextrin. The characteristic forming of inclusion complex in solid dispersion system wasevaluated by infrared analysis and then followed by HyperChem molecular model analysis. Thedissolution test was done in order to see the increasing of dissolution rate and this test is usedbuffer phosphate pH 5,8 as the medium with rotation speed 100 rpm at 37 ± 0,50C for 60 minutes.The amount of dissoluted furosemide was then analyzed by spectrophotometric test. Thedissolution parameter with Dissolution Efficiency (DE) is conducted in 10, 30, and 60 minutes. Thedata were analyzed with Two Way ANOVA at p